APPLICATION OF THE SAW METHOD IN THE DECISION SUPPORT SYSTEM FOR NEW STUDENTS AT SMAK ST. ANPHONSUS - Imelda Dengi Walu; Gergorius Kopong Pati (CV. Fahr Publishing, 2023)
Admission of new students is an activity that must be carried out by every school. To support the quality of the school, in the process of admitting new students there is a prospective student selection process which is carried out to select prospective students according to the criteria determined by the school. Likewise with SMAK St. Anfonsus, who selects prospective students. It's just that the results of the selection are sometimes imprecise and inaccurate because they do not match the criteria determined by the school. Based on the existing problems, a decision support system is needed that functions as a tool to help SMAK St. Anfonsus in the selection process for new student admissions uses the Simple Additive Weighting (SAW) method. Because this method is suitable for the decision-making process in the selection of new student admissions because it can determine the weight value for each criterion, then proceed with a chaining process that will select the best alternative.